Day Immunity Enrichment of Freshwater Catfish Gulsa (Mystus cavasius) by Supplement Dietary Inclusion of Black Cumin Seed (Nigella sativa) (Journal of Science and Technology Research, 2026)
The present study was undertaken to evaluate the effects of dietary black cumin Nigella  sativa seed on growth performance, feed utilization and disease resistance in freshwater  catfish gulsa (Mystus cavasius) against the pathogenic bacteria Aeromonus hydrophila.  Fish (1.2±0.07 g) were fed with experimental diet, containing control as commercial  feed, black cumin seed powder (BCP) 1%, and black cumin seed extract (BCE) 0.5% for  90 days culture period. After 90 days, 10 fish from each treatment group, in triplicate,  were challenged with the pathogenic bacteria Aeromonas hydrophila via intraperitoneal  injection. The fish were then monitored daily for 7 days to observe clinical signs and  record mortality rates. The growth parameters, including weight gain, specific growth  rate, protein efficiency ratio, and survival rate, showed a significant increase (p